2010
DOI: 10.1161/circgenetics.109.897793
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of the CCR5 Region With Lipid Levels in At-Risk Cardiovascular Patients

Abstract: Background-There is mounting evidence to suggest that chemokine receptor 5 (CCR5) plays an important role in the development and progression of atherosclerosis. A naturally occurring variant of the CCR5 gene CCR532, exists at allele frequencies of typically 10% in European populations and results in a nonfunctional CCR5 receptor. Methods and Results-The CCR5⌬32 deletion and 26 other variants within the chemokine receptor 2-CCR5-chemokine receptor-like protein 2 (CCRL2) gene cluster spanning 59 kilobases of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…People homozygous for CCR5Ä32 are naturally resistant to R5 HIV infection and the heterozygous state is associated with up to 2-4 years delay in disease progression (Gupta & Padh, 2012). This polymorphism was found in Caucasians and in Chinese state high (Liu et al, 2012) and exists at allele frequencies of typically 10% in European populations (Hyde et al, 2010). However, to our knowledge, the presence of CCR5Δ32 polymorphisms in Indonesian HIV patients has not been reported.…”
Section: Introductionmentioning
confidence: 73%
“…People homozygous for CCR5Ä32 are naturally resistant to R5 HIV infection and the heterozygous state is associated with up to 2-4 years delay in disease progression (Gupta & Padh, 2012). This polymorphism was found in Caucasians and in Chinese state high (Liu et al, 2012) and exists at allele frequencies of typically 10% in European populations (Hyde et al, 2010). However, to our knowledge, the presence of CCR5Δ32 polymorphisms in Indonesian HIV patients has not been reported.…”
Section: Introductionmentioning
confidence: 73%
“…In contrast to eotaxin‐1 and MCP‐1, MIP‐1β levels were not associated with lipid profile or insulin resistance, rather MIP‐1β strongly correlated with CRP and less so with MCP‐1. Accumulating evidence suggests a role for MIP‐1β and its receptor, CCR5, in the pathogenesis of atherosclerosis . Indeed, they may be involved, not only in the recruitment of peripheral monocytes to the developing plaque, but also in adipose tissue dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Among hypertensive subjects, those in the top quartile for serum MIP‐1β were at increased risk of stroke and cardiovascular events over a mean follow‐up period of 37 months . Furthermore, it has been observed that a naturally occurring variant of CCR5 gene, CCR5Δ32 a 32 bp deletion that leads to a non‐functional receptor, is associated with increased plasma HDL and decreased TG in cohorts with established cardiovascular disease …”
Section: Discussionmentioning
confidence: 99%
“…We raise this point as the polymorphism in the non-coding region of CCR5 that is shared by HHG*1 and HHG*2 and which distinguishes it from all the other CCR5 haplotypes (named as A29G in Figure 1) is in nearly 100% linkage disequilibrium with a polymorphism in a haplotype of CCRL2 (www.hapmap.org and data not shown) that is ∼31 kb downstream of CCR5 . Recent studies have demonstrated that this CCRL2 haplotype associates with multiple diseases [33], [34].…”
Section: Discussionmentioning
confidence: 99%